PENGARUH PROGRAM BANTUAN BIBIT DAN PUPUK TERHADAP PENDAPATAN PETANI PADI DI KABUPATEN BONE BOLANGO - Dhea Amalia R. Ali; Zain Olilingo, Fahrudin; Hadi Yulia Akib, Fitri (Jurnal Paradigma Ekonomika, 2025)
This study analyzes the effect of seed and fertilizer assistance programs on the income of rice farmens in Bone Bolango Regency. The study employed a quantitative approach with a multiple linear regression method, based on primary data from 90 farmers selected through an accidental sampling technique. The regression coefficient for the seed assistance variable is 0.395 with a significance value of 0.000, whereas the coefficient for the fertilizer assistance is 0.576 with a significance value of 0.000. This suggest that each increase in the quantity or quality of seed and fertilizer assistance can have a significant effect on farmens’ income. Thus, the policy of providing agricultural production inputs such as seeds and fertilizers has proven effective in increasing farmers’ income.